Leaf gas exchange and competitive ability of Zea mays and Sorghum halepense as affected by water competition - Acciaresi, Horacio Abel (2012)
In an environment involving water deficit and competition, weed species may show inefficient water use. The aim was to determine the water consumption strategy of Zea mays and Sorghum halepense and the effects of these strategies on crop and weed competitive ability.Under two soil water availability conditions, the soil and leaf water potential (Ψ), relative water content (RWC) and leaf gas exchange parameters were measured during the critical period of crop competition in pot experiments where Z. mays and S. halepense were grown alone or in competition. In addition, the relative yield total and aggressivity index of both species were calculated.S. halepense showed continuous absorption of water, reaching a lower Ψ than the Z. mays hybrids. S. halepense maintained a RWC of above 90%, which only decreased to 70% in the case of competition for low water supplies. In Z. mays, RWC declined to values of 70% at both water levels. S. halepense exhibited active leaf gas exchange. Z. mays hybrids had lower competitive ability than S. halepense at both competition levels due to their conservative water use strategy. Sustained water use by the weed could be the cause of the increased aggressivity of S. halepense under water deficit conditions.